2016
DOI: 10.1016/j.ajpath.2015.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Inhibitor of κB Kinase β Prevents Inflammation-Induced Preterm Delivery by Inhibiting IL-6 Production from Amniotic Cells

Abstract: Preterm delivery (PTD) remains a serious challenge in perinatology. Intrauterine infection and/or inflammation, followed by increased inflammatory cytokines, represented by IL-6, are involved in this pathology. Our aim was to identify IL-6-producing cells in the placenta and to analyze the potential of targeting IκB kinase β (IKKβ) signaling to suppress IL-6 production for the treatment of PTD. Immunohistochemical analyses using placentas complicated with severe chorioamnionitis revealed that IL-6 is mainly ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 55 publications
(75 reference statements)
1
15
0
Order By: Relevance
“…In support of this notion, IL-1 and TNF-α administration induced both preterm labor and intermediate steps in the labor cascade, and genetic disruption of IL-1 or TNF-α receptors significantly prevented LPS-induced PTL [ 59 61 ]. In addition, the inhibition of IL-6 signaling or IL-6 production suppressed LPS-induced PTL [ 30 , 62 ]. On the contrary, the absence of IL-10, a major anti-inflammatory cytokine, exaggerated LPS-induced PTL with elevated expression of inflammatory cytokines such as IL-1, IL-6 and TNF-α [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…In support of this notion, IL-1 and TNF-α administration induced both preterm labor and intermediate steps in the labor cascade, and genetic disruption of IL-1 or TNF-α receptors significantly prevented LPS-induced PTL [ 59 61 ]. In addition, the inhibition of IL-6 signaling or IL-6 production suppressed LPS-induced PTL [ 30 , 62 ]. On the contrary, the absence of IL-10, a major anti-inflammatory cytokine, exaggerated LPS-induced PTL with elevated expression of inflammatory cytokines such as IL-1, IL-6 and TNF-α [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the resident cells of the chorion and decidua are capable of synthesizing and secreting IL-6, and its production is stimulated by LPS or proinflammatory factors such as IL-1 β and TNF- α [ 35 ]. Furthermore, another study has demonstrated that IL-6 secretion is upregulated in fetal membranes of preterm pregnancies, indicating that IL-6 might be a key factor in accelerating the events of preterm birth [ 36 ]. Therefore, it is understandable that the change of IL-6 is the most obvious one among these markers.…”
Section: Discussionmentioning
confidence: 99%
“…These findings indicate that amnion mesenchymal cells can mediate immune responses. Immunohistochemical analyses have shown that infected placentas contain mesenchymal cells with high levels of IL-6 expression [10]. Moreover, stimuli such as IL-1β, IL-6, thrombin, fibronectin and LPS from Escherichia coli have been reported to activate NF-κB, enhance COX-2 mRNA expression and increase prostaglandin E 2 production in mesenchymal cells but not epithelial cells [9][10][11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…Amnion cells were characterized using antibodies specific for two different filament proteins: cytokeratin-18 (a marker of epithelial cells) and vimentin (a marker of mesenchymal cells). Immunostaining was performed using primary antibodies against cytokeratin-18 (1:15,000; Abcam, Cambridge, UK) and vimentin (1:3000; Cell Signaling Technology, Danvers, MA, USA), as described in a previous report [10]. Amnion epithelial cells displayed a cobblestone-like morphology and were positive for cytokeratin-18 and negative for vimentin.…”
Section: Isolation and Culture Of Epithelial And Mesenchymal Cells From Human Amnionmentioning
confidence: 99%
See 1 more Smart Citation